Sonochemical synthesis of CQDs from coffee husk: Insights in aggregation mechanism, optimization and sustainability analysis - Alfonso Enrique Ramírez Sanabria; Santiago Urbano Narváez; Johnny Vilard Gutiérrez Portilla; Gerardo Andres Torres Rodríguez (Heliyon)
A green methodology for the synthesis of carbon quantum dots (CQDs) from coffee husk without the use of any toxic solvents is proposed in this work. Sonochemical exfoliation of biochar, obtained from the thermal carbonization of coffee husk (from a certified coffee seeds) at low temperature in an air-restricted atmosphere, is described as an alternative procedure for the sustainable production of CQDs. The synthesized CQDs exhibited blue fluorescence with a strong maximum emission band at 410 nm when excited at a maximum absorption wavelength of 330 nm. The obtained CQDs were evaluated by various physicochemical methods. According to the results, TEM investigation indicates the average size of CQDs is 8.27 ± 1.57 nm with a quasi-spherical morphology. The aim of this study is to optimize the synthesis parameters and compare them with common preparation strategies. This paper reports the main requirements for reproducible and scalable production of CQDs solution, such as the mass of the precursors for each process, for the first time. The conversion and yield percentages on a dry basis, mass of CQDs powder agglomerates, and the specific time duration for each individual step are provided to compensate for the variability of the raw material and facilitate statistical comparison of the methodology. A TEM micrographs analysis for CQDs reconstitution process was conducted, which can be considered a potential mechanism for CQDs agglomeration process.